Some Fixed Point Results on Multiplicative Metric Spaces - Ahmad Ansar; Muh. Akbar Idris (Program Studi Matematika Universitas Sulawesi Barat, 2022)
In this paper, we first discussed some results about multiplicative metric spaces to support the main results. The aim of this paper is to present fixed point some result that satisfied some generalized of contraction mapping related to multiplicative metric spaces. Furthermore, some examples are given to support results